Planting density influence on fibrous root reinforcement of soils - Loades, K. W.; Bengough, A. G.; Bransby, M. F.; Hallett, P. D. (Ecological Engineering, 2010)
Reinforcement of soil by fibrous roots is crucial for preventing soil erosion and degradation, yet the underlying mechanisms are poorly understood. We investigated soil reinforcement by roots of barley (Hordeum vulgare) planted at different densities in a controlled glasshouse and a separate field study. Soil shear strength increased with planting density (0-950 m(-2)) at 5 weeks with an average 6.7 +/- 1.40 kPa increase in strength over the fallow (7.5 +/- 0.47 kPa). At 20 weeks, planting density had less of an effect, with on average a 29% increase in strength contributed by roots. In the glasshouse study, roots increased shear strength by an average of 53%, with a positive effect found for the eight planting densities tested ranging from 0 to 1130 plants/m(2). Detailed measures of root tensile strength, and diameter distributions at the shear plane, allowed us to apply and test two existing root reinforcement models of Wu et al. [Wu, T.H., Mckinnell, W.P., Swanston, D.N., 1979. Strength of tree roots and landslides on Prince-Of-Wales-Island, Alaska. Canadian Geotechnical journal 16,19-33] and Pollen and Sinion [Pollen, N., Simon, A., 2005. Estimating the mechanical effects of riparian vegetation on stream bank stability using a fiber bundle model. Water Resources Research, 41]. A progressive failure Fibre Bundle Model, developed by Pollen and Simon [Pollen, N., Simon, A., 2005. Estimating the mechanical effects of riparian vegetation on stream bank stability using a fiber bundle model. Water Resources Research, 41], predicted reinforcement better than the catastrophic failure model by Wu et al. [Wu, T.H., Mckinnell, W.P., Swanston, D.N., 1979. Strength of tree roots and landslides on Prince-Of-Wales-Island, Alaska. Canadian Geotechnical journal 16, 19-33], but neither described reinforcement well for field-grown plants near maturity at 20 weeks. (C) 2009 Elsevier B.V. All rights reserved.